Facial Feedback: Limited Effect for Videos of Opposite Emotions - FABIANO KOICH MIGUEL (Revista Colombiana de Psicología, 2016)
To prove the hypothesis of facial feedback (FF) for opposite emotional stimuli, 30 participants viewed a happy video, with 15 of the participant posing a sad expression; another 30 participants viewed a sad video, with 15 posing a joyful expression. Levels of joy, sadness, anger and anxiety were recorded before and after the videos. All observers of the happy video showed a decrease in sadness, but those who posed for sadness expressed lesser decrease. For their part, participants who posed joy during the sad video recorded an increase in anger and anxiety, attributed to having to pose for joy. No evidence was found that FF can counteract the effects of an intense emotional stimulus. The evidence related to the controlling of the intensity of an opposite emotion was also limited. The study found that posing for joy while undergoing sadness could provoke other negative emotions. The study questions the practical usefulness of FF.